Lobular capillary hemangioma with an intraosseous feeder vessel through an accessory buccal foramen in the mandible: A unique case report - Subash Chandra Raj; Asit Kumar Mishra; Shaheda Tabassum; Debajani Baral (Wolters Kluwer Medknow Publications, 2024)
The aim of this case report is to present a unique and rare finding in a 29-year-old male with the chief complaint of swelling in the gums related to the back teeth of the lower left jaw, since 20 days. In the absence of any alarming findings on the intraoral periapical radiograph and blood profile, an excisional biopsy of the provisionally diagnosed pyogenic granuloma was planned with a high-power diode LASER (Light Amplification by Stimulated Emission of Radiation). Following the excision, an unusual amount of bleeding was encountered from a single point on the buccal cortical plate between the teeth #35 and #36. On reevaluating the left face with advanced radiodiagnostic methods, an accessory buccal foramen was reported distal to #35 which housed a thin, tortuous, and aberrant branch of the inferior alveolar artery. The swelling was histopathologically diagnosed as lobular capillary hemangioma, and the aberrant artery was labeled as its feeder vessel. The patient had no episode of recurrence until 2 years of follow-up.